Eat, Sleep, Console and Adjunctive Buprenorphine Improved Outcomes in Neonatal Opioid Withdrawal Syndrome. (February 2021) - Hein, Sarrah; Clouser, Barbara; Tamim, Mohammed M.; Lockett, Diane; Brauer, Kathleen; Cooper, Linda
Abstract : Background: The worsening opioid crisis has increased the number of infants exposed to maternal opioids. Standard treatment of newborns exposed to opioids prenatally often requires prolonged hospitalization and separation of the mother–infant dyad. These practices can potentially increase severity of withdrawal symptoms, interrupt breastfeeding, and disturb mother–infant bonding. Use of the Eat, Sleep, Console (ESC) model may ameliorate symptoms, decrease mother–infant separation, and decrease hospital length of stay. Purpose: To manage opioid exposed infants in a more holistic manner to decrease neonatal intensive care unit (NICU) admissions, reduce the need for pharmacotherapy, and evaluate response and total length of treatment after a unit protocol change from morphine to buprenorphine. Methods: Implemented ESC model, optimized nonpharmacologic bundle, and prescribed buprenorphine therapy instead of morphine as needed for adjunctive therapy. Results: Admissions of opioid-exposed infants from the Mother–Baby Unit (MBU) to the NICU decreased by 22%, and the number of infants who required pharmacotherapy was reduced by 50%. The average length of pharmacotherapy fell from 14 to 6.5 days. Implications for Practice: The successful implementation of the ESC model helped keep the mother–infant dyad together, reduced admissions to the NICU, and lessened the need for pharmacotherapy. The change to buprenorphine further reduced our average length of treatment. Implications for Research: Investigation of monotherapy with buprenorphine needs to be evaluated as a valid treatment option. The buprenorphine dosing and weaning chart will need to be revised and modified if indicated.